Evaluation of coal export from Russia - A. V. Korolyatin; Yu. N. Linnik (Вестник университета)
Dynamics of coal mining in Russia and also export of coal from Russia has been presented. Demand for the Russian coal has been analyzed, reasons for refusal of some countries of extraction of own coal have been revealed. Challenges of the coal industry on medium and long term have been determined and perspectives for its development have been planned. Based on the study, the possible threats to the Russian coal market have been identified and the main competitors of Russia in the field of coal export have been considered.